IN VIVO AND IN VITRO ANTILEISHMANIAL EFFECTS OF METHANOLIC EXTRACT FROM BARK OF BURSERA APTERA - Nieto-Yañez, O. J.; Resendiz-Albor, A. A.; Ruiz-Hurtado, P. A.; Rivera-Yañez, N.; Rodriguez- Canales, M.; Rodriguez-Sosa, M.; Juarez-Avelar, I.; Rodriguez-Lopez, M. G.; Canales-Martinez, M. M.; Rodriguez-Monroy, M. A. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Cutaneous leishmaniasis lacks effective and well-tolerated treatments. The current therapies mainly rely on antimonial drugs that are inadequate because of their poor efficacy. Traditional medicine offers a complementary alternative for the treatment of various diseases. Additionally, several plants have shown success as anti-leishmanial agents. Therefore, we sought to evaluate the in vitro and in vivo activity of MEBA against Leishmania mexicana. Materials and Methods: Methanolic extract of B. aptera was obtained by macetration, after we determined in vitro antileishmanial activity of MEBA by MTT assay and the induced apoptosis in promastigotes by flow cytometry. To analyze the in vivo anti-leishmanial activity, we used infected mice that were treated and not treated with MEBA and we determined the levels of cytokines using ELISA. The phytochemical properties were determined by CG-MS and DPPH assay. Results: We determined of LC50 of 0.408 mg/mL of MEBA for in vitro anti-leishmanial activity. MEBA induced apoptosis in promastigotes (15.3% ± 0.86). Treated mice exhibited smaller lesions and contained significantly fewer parasites than did untreated mice; in addition, we found that IFN-γ and TNF-α increased in the sera of MEBA-treated mice. GC-MS analysis showed that podophyllotoxin was the most abundant compound. Evaluation of the activity by DPPH assay demonstrated an SC50 of 11.72 μg/mL. Conclusion: Based on the above data, it was concluded that MEBA is a good candidate in the search for new antileishmanial agents.